Energy concentrate supplementation accelerates dung decomposition and soil element turnover in grazing sheep - Xuan Wang; Xulei Liu; Lijuan Ran; Fujiang Hou (Soil and Tillage Research, 2026)

Selective enrichment of fractions in thermal dissolution of high-sulfur coal: Application of solid-phase microextraction technology and construction of ZnO/rGO coatings - Jia-Qi Liu; Xing Fan; Ran-Ran Hou; Xiao-Hui Cao; Binoy K. Saikia; Chao Feng; Jin-Xi Wu; Xiao-Yu Dong (Fuel, 2026)

Institutional configurations and conservation agriculture outcomes: A fuzzy-set analysis of production units in Lishu County, China's black-soil region - Hongwei Yu; Yufeng Hou; Youchao Xing; Huixin Ran; Chuanling Xiang; Mingze Xia; Zijie Liu; Hu Zhou (Land Use Policy, 2026)

An ultrathin triazine-anchored hypercrosslinked and nonflammable solid polymer electrolyte for safe Li metal batteries - Ran Wang; Yongle Yan; Zelin Lv; Xiaoxiao Li; Xutao Liang; Yang Gao; Mengchao Li; Lifeng Hou; Shi Wang; Zhong Jin; Qian Wang (Chemical Engineering Journal, 2026)

Long-term greenhouse cultivation reduces soil multifunctionality by weakening microbial network stability through decreased network complexity - Dongrui Qin; Yimei Huang; Zhuonan Hou; Xinnian Guo; Taishan Ran; Wenqian Han (Applied Soil Ecology, 2026)

Targeting viral Fe-S clusters with TEMPOL confers broad-spectrum anti-coronavirus activity - Leyu Hu; Lexi Gao; Xingwei Fu; Zesheng Rong; Yue Cheng; Yuhan Hou; Lu Han; Xin Ran; Guiwen Guan; Ting Zhou; Lingling Chang; Xiaomin Zhao; et al. (Veterinary Microbiology, 2026)

Macroscopic crack ratio as a structural surrogate linking linear filtration and nonlinear expression in sludge dewatering - Yi-Wen Yuan; Hao-Ran Chen; Zhi-Hao Liu; Shi-Yu Ren; Chang-Ji Huang; Raymond Jianxiong Zeng; Hou-Feng Wang (Process Safety and Environmental Protection, 2026)

Long-term petroleum pollution alters soil microbial communities via electron transfer capacity: Evidence from a 35-year chronosequence - Chengze Yu; Mingxiao Li; Jun Cui; Yanjun Xin; Ran Song; Wangmi Chen; Jiaqi Hou; Jianbing Li; Huibin Du; Beidou Xi (Journal of Environmental Sciences, 2026)

Complex enzymolysis-derived peanut peptides: in silico selection of antioxidant peptides, emulsion-microcapsule encapsulation, and in vitro digestive performance evaluation - Chengli Jia; Yansheng Wang; Tiantian Ran; Zhiqing Gong; Wenjia Cui; Shasha Song; Jian Zhang; Furong Hou; Junyan Shi; Fengjuan Jia; Wenliang Wang (Food Research International, 2026)

Ultraconductive carbon film/fiberboard heterostructure integrating superior EMI shielding and efficient joule heating - Ziyi Yin; Ran Wang; Yansong Wang; Yi Hou; Yang Hu; Shiyue Tang; Zhijiang Wang; Xiaolin Lan; Zhanhua Huang (Chemical Engineering Journal, 2026)

Effects of microbivorous nematodes on microbial necromass accumulation under changing precipitation in tropical forests - Qiongjie He; Ning Zhao; Kangle Hou; Qiang Ran; Rentao Liu; Faming Wang; Feng Sun; Yakov Kuzyakov (Applied Soil Ecology, 2026)

Impact of waste biomass binders on the pelletizing, combustion, and engineering feasibility of sludge–coal slime co-pelletized fuel - Hao-Ran Chen; Yi-Wen Yuan; Zhi-Hao Liu; Chang-Ji Huang; Shi-YuS Ren; Hou-Feng Wang; Raymond Jianxiong Zeng (Environmental Research, 2026)

Shear behaviour of CFRCM-jacketed seawater sea sand concrete beams under an integrated ICCP-SS system - Panpan Liu; Linbing Hou; Ran Feng; Youhua Fan; Ji-Hua Zhu (Engineering Structures, 2026)

Dual-enhancement strategy for high-performance multimodal hydrogel sensors in deep learning-assisted speech recognition systems - Xiang Di; Liqi Li; Yi Wang; Weiqiang Ran; Zihan Chen; Yaning Feng; Bo Yu; Jiawen Hou; Di Chen; Chungang Yuan (Chemical Engineering Journal, 2026)

Compost Substrate Formulations Reshape Soil Physicochemical Properties and Rhizosphere Microbiota: A PLS-SEM Analysis - Chuang Liu; Ran Luo; Ruitong Niu; Senxi Hou; Zihao Zhang; Yumeng Li; Yingxue Zhou (Journal of Soil Science and Plant Nutrition, 2026)

Retraction notice to “Variations and driving factors of leaf functional traits in the dominant desert plant species along an environmental gradient in the drylands of China” [Sci. Total Environ. 897 (2023) 165394] - Muhammad Adnan Akram; Xiaoting Wang; Nawal Shrestha; Yahui Zhang; Ying Sun; Shuran Yao; Jinhui Li; Qingqing Hou; Weigang Hu; Jinzhi Ran; Jianming Deng (Science of The Total Environment, 2026)

Asymmetric spectral modulation of bioinspired Janus metafabric toward environment-adaptive thermal and moisture management under extreme conditions - Yang Wu; Long Zhang; Hao-Ran Yang; Jiaqi Li; Yuzhen Hou; Chang-Shun Li; Bobo Shi; Meng Zhou; Wulin Shang; Weiqing Kong; Huan Xu; Gang Zhou; et al. (Chemical Engineering Journal, 2026)

A degradable, highly tough, and resilient nanocomposite hydrogel for self-powered wearable sensors and a deep learning-assisted recognition system - Xiang Di; Weiqiang Ran; Yi Wang; Ruotong Zhang; Bo Yu; Baohui Li; Jiawen Hou; Chungang Yuan (Chemical Engineering Journal, 2026)

Hydrocarbon charging dynamics and its coupling with reservoir densification in a tight sandstone system: Insights from the Jurassic of the Yangxia Sag, Kuqa Depression - Chang-chao Chen; Jun Li; Jinz-hou Wang; Ling Li; Hao-ran Gao; Zheng-lian Pang; Xiu-yan Chen; Min Yang (Applied Geophysics, 2026)

Single-cell transcriptomic analysis identifies a MIF-driven keratinocyte-macrophage-Th2 axis as a key inflammatory circuit in atopic dermatitis - Yan Wei; Rui-Min Bai; Hao-Ran Guo; Jin Shan; Li-Juan Wang; Yan Zhou; Kuan-Hou Mou; Yan Zheng; Ya-Guang Zhang (Inflammation Research, 2026)

Tuning the thermal reactivity of low-rank coal: The structural role of phenolic hydroxyl groups from molecular aggregation to pore collapse - Hao Xu; Jin-Xi Wu; Yu-Hong Kang; Xing Fan; Ya-Ya Ma; Guang-Hui Liu; Ran-Ran Hou; Zhong-Qiu Liu; Wen-Long Mo; Yao Lu (Fuel, 2026)

Ectoine modulates mixotrophic denitrification pathway partitioning to sustain stable nitrogen and phenol removal under hypersaline stress - Jingwen Song; Ya-Nan Hou; Ran Li; Zengyue Feng; Ai-Jie Wang; Nanqi Ren; Wei Wei; Bing-Jie Ni; Cong Huang (Water Research, 2026)

Unlocking the effects of cold plasma on enhancing the stabilization of oat flour: Insights from storage characteristics, lipidomics, and flavor analysis - Shunzhang Ma; Hao Ran; Jinquan Lin; Yuanlin Sun; Lizhen Zhang; Fang Zhong; Sumei Zhou; Dianzhi Hou (Journal of Stored Products Research, 2026)

Operational threshold and associated mechanisms in composting remediation of diesel-contaminated soils - Chengze Yu; Haipeng Huang; Ran Song; Jiaqi Hou; Huibin Du; Mingxiao Li; Yanjun Xin; Beidou Xi (Journal of Environmental Management, 2026)

Decoding the molecular complexity of coal: A machine learning framework for component classification and solvent selection - Yu-Ying Zhou; Xing Fan; Jin-Xi Wu; Zhen-Yu Gao; Ran-Ran Hou; Chao Feng; Zhong-Qiu Liu; Qing Liu; Xiao-Yu Dong; Peng Liang (Fuel, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Redox-active co-pyrolytic carbon enhances electron transfer and mitigates petroleum hydrocarbon hazards in contaminated soils - Chengze Yu; Haipeng Huang; Ran Song; Jiaqi Hou; Huibin Du; Mingxiao Li; Yanjun Xin; Beidou Xi (Journal of Hazardous Materials, 2026)

Three centuries of human impact: A comprehensive framework for assessing landscape dynamics and environmental consequences in the Great Lake Basin - Zhongwu Li; Yinglong Hou; Lingxia Wang; Wenqing Li; Hui Wang; Fengwei Ran; Xinyu Ling; Xiaodong Nie (Journal of Environmental Management, 2026)

Distinct profiles and elevated exposure to liquid crystal monomers in urban areas: Insights from indoor dust across China - Ye-Yang Hou; Da-Jian Li; Shi-Yang Liu; Peng-Ran Guo; Liang-Ying Liu (Environmental Research, 2026)

Cross-scale modeling of bacteria-contaminant spatiotemporal dynamics in 3D bioprinted hydrogel for dye biodegradation - Weihao Guo; Ya-Nan Hou; Wei Xing; Ran Xu; Jinfeng Ma; Ai-Jie Wang; Nanqi Ren; Cong Huang (Bioresource Technology, 2026)

Revegetation mechanisms and influence factor in alpine mining areas: a case study of the Muli mining area, Qinghai-Tibet Plateau - Kaixin Zhang; Qingqiu Hou; Haibo Feng; Linxue Ju; Jianwei Zhou; Jun Li; Ruimin Xiong; Yi Zhu; Xiaoming Zheng; Ran Li; Chunguang Wang (Plant and Soil, 2026)

Nonlinear threshold response and erosion-driven pathways of sediment organic carbon to anthropogenic activities in a large lake - Fengwei Ran; Tao Xiao; Zhongwu Li; Shilan Wang; Yinglong Hou; Haipeng Wu; Xiaodong Nie (Anthropocene, 2026)

A chlorinated 2-(2-phenylethyl)chromone in artificial agarwood as a DRD5 agonist and mediates the cAMP/Ca²⁺ signaling pathway to intervene in the growth and proliferation of gastric cancer cells - Zi-Xiao Jiang; Jian Feng; Wen-Cheng Hou; Mei-Ran Wang; Shu-Nan Zhang; Yang-Yang Liu (Phytochemistry Letters, 2026)

Bioinformatics-based discovery of a new norsesquiterpenoid from agarwood targeting CHRM2 and regulating the PI3K-Akt pathway in liver cancer - Zi-Xiao Jiang; Jian Feng; Wen-Cheng Hou; Mei-Ran Wang; Shu-Nan Zhang; Hao-Jie Liang; Yang-Yang Liu (Phytochemistry Letters, 2026)

Determining the age of Guadalupian extinction by in situ uranium–lead geochronology in regard to middle Permian giant bivalve Alatoconchidae fossils in the Northwest margin of the South China Plate - Xueqin Zhao; Ran Liu; Fudong Wang; Qian Li; Chen Su; Jiaming Ding; Caifu Xiong; Wentao Li; Jianhua Zhang; Keli Hou (Gondwana Research, 2026)

Synthesis, evaluation and preliminary clinical study of novel 68Ga-labeled Nectin-4 targeting PET tracer - Geng Hu; Zexin Xu; Da-Yong Hou; Pengcheng Ran; Liang Cheng; Wei Liu; Yue Zhao; Fan Jia; Xinyue Yang; Huihui You; Baoyuan Li; Hongxin Li; et al. (Chemical Engineering Journal, 2026)

Rhein Prevents APAP-induced drug-induced Liver Injury by Upregulating Nrf2 and Inhibiting APAP-activating Enzymes - Mingda Liu; Jin Dai; Liangding Dou; Zifeng Deng; Junxian Liu; Xin Hou; Jinwen Zhang; YongChao Huang; Zhi Huang; Dai Wang; Dongbei Guo; Ran An; et al. (Cell Biochemistry and Biophysics, 2026)

MHC II system of mandarin fish (Siniperca chuatsi): Gene identification, expression analysis and transcriptional regulation - Jing Hou; Lu Qi; Ran Cao; Lan Hao Liu; Shan Nan Chen; Pin Nie (Aquaculture, 2026)

Effectiveness and optimization strategies for contaminant remediation using integrated groundwater circulation well and pump-and-treat methods in heterogeneous aquifer - Zaiyong Zhang; Bin Ran; Yu-Li Wang; Chuanqi Zhang; Pengze Hou; Jiamin Shao; Jingbo Yang; Chengcheng Gong (Process Safety and Environmental Protection, 2026)

Enhanced bacteria-fungi associations and soil microbial network stability underpin ecosystem multifunctionality across a 53-year desert restoration chronosequence - Qingqing Hou; Muhammad Aqeel; Longwei Dong; Jie Peng; Ying Sun; Fan Li; Dong Tang; Bodong Yuan; Xusheng Guo; Jinzhi Ran; Weigang Hu; Xinrong Li; et al. (Journal of Environmental Management, 2026)

Functional native herbage (Capparis spinosa L.) modulates rumen fermentation and antioxidant capacity in grazing sheep by optimizing rumen microbial composition - Xuan Wang; Lijuan Ran; Fujiang Hou (Animal Feed Science and Technology, 2026)

High-performance and fast fiber-optic SPR gas sensor based on WO3/SnO2 nanocomposites films for room-temperature NH3 detection - Chong Li; Yan Wang; Jinqiao Hou; Huanming Wang; Jingting Luo; Chen Fu; Fujian Ren; Jikai Zhang; Huiling Ong; Chenze Lu; Hang Xiao; Xi Chen; et al. (Journal of Environmental Chemical Engineering, 2025)

Superior degradation of endocrine disruptors over defective iron pyrites assisted by vacancy-induced disassociation of hydrogen peroxide - Han-Liang Fang; Yu-Hang Xu; Xiang-Min Jin; Hao-Ran Long; Wen-Ni Zhang; Han-Hui You; Zhou Zhong; Yi-Dong Hou; Hai-Lei Cao; Christopher Rensing; Jian Lü (Chemical Engineering Journal, 2025)

The Increased Effect of Spring Leaf Unfolding on Autumn Senescence in the Northern and Southern Hemispheres - Dong Tang; Shubin Xie; Jie Peng; Ying Sun; Abraham Allan Degen; Yuan Sun; Jiali Luo; Zifan Li; Yaning Kuang; Lixue Wei; Weigang Hu; Longwei Dong; et al. (Global Ecology and Biogeography, 2025)
Aim To investigate the contributions of vegetation growth carryover (VGC, defined as the effect of present states of vegetation growth on subsequent phenophases) and climatic factors to plant phenology, particularly start‐of‐season (SOS) and end‐of‐season (EOS), and how these contributions have evolved globally over the past four decades. Location Global, with a focus on the Northern Hemisphere (NH) and Southern Hemisphere (SH). Time Period 1963–2015 for ground observations, 1982–2022 for satellite NDVI data, and 1982–2022 for climate data (temperature, precipitation, radiation, and potential evapotranspiration). Major Taxa Studied Global vegetation, without specifying individual species. Methods We analysed two sets of satellite‐derived NDVI data, ground‐based phenological observations, and long‐term climate data (temperature, precipitation, radiation, and potential evapotranspiration). Statistical models quantified the contributions of climatic factors and VGC to phenology trends. Results Globally, advanced SOS was driven primarily by increasing temperature and radiation, while delayed EOS was attributed to rising temperature and the carryover effect of spring vegetation growth (VGC SOS ). VGC SOS was the dominant driver of EOS in the SH, whereas temperature played a larger role in the NH. Over the past four decades, the contribution of VGC SOS to EOS has increased significantly on a global scale. However, the SH experienced pronounced “warming and drying” trends, which weakened the relative contribution of VGC SOS to EOS compared to climate‐driven delays. Main Conclusions VGC SOS plays a substantial role in shaping EOS in both hemispheres, with its importance increasing over time. These findings improve our understanding of vegetation dynamics and offer valuable insights for predicting vegetation growth and carbon sequestration under future global warming scenarios.

Przewalskia tangutica dietary supplementation enhances performance, modifies grazing behavior, and mitigates methane emissions in sheep on saline-alkali pastures - Xiaoyun Zhang; Lijuan Ran; Kaili Xie; Fujiang Hou (Animal Feed Science and Technology, 2025)

Periostin enhances paracrine effect of adipose-derived stem cells on chondrocyte proliferation, adhesion and migration - Ran Lu; Yong Hou; Xiaogao Wang; Zeyu Guan; Zhonglin Nie; Chaowen Yu; Yong Gao (Tissue and Cell, 2025)

Plasma-catalytic degradation of dimethyl disulfide over peroxydisulfate-intercalated CoFe-LDH: Synergistic effects and mechanistic insights - Yuqi Zhang; Ran Sun; Yuhang Zhong; Hui Xu; Yujie Tan; Jianyuan Hou; Yuan Yuan; Xingang Liu; Renxi Zhang (Journal of Hazardous Materials, 2025)

A ratiometric fluorescent probe for sensitive detection of benzoyl peroxide and hypochlorite in food - Shun-Qiang Cui; Xin-Yi Liang; Zhi-Qiang Cai; Hou-Qun Yuan; Qiu-Yu Zhang; Yi-Fan Xia; A.K.I.M.A.N.A. Sandra; Ling-Yi Guo; Ran Wang; Shi-Yu Zhao; Yan-Xia Li; Guang-Ming Bao (Food Chemistry, 2025)

Multifunctional bending sensor based on PLA hierarchical porosity: smart wearable device with wide range response, self-powered capability and biodegradable - Jun Hou; Danqing Zhang; Qi Ran; Geran Yin; Manlin Wang; Wenhao Yang; Hua Wang; Yi Xiong; Xin Liu; Heng Pan; Liangjun Xia; Weilin Xu (Chemical Engineering Journal, 2025)

MoS2 nanosheets engineered with recycled cobalt for enhanced activation of peroxymonosulfate - Mengke Fan; Kun Zhang; Xiang Gu; Yanrun Mei; Ran Chen; Jingping Hu; Huijie Hou; Jiakuan Yang (Chemical Engineering Journal, 2025)

Unveiling the differences between vitexin and isovitexin: From the perspective of sources, green advanced extraction technologies, biological activities, and safety - Jinquan Lin; Hao Ran; Qiqian Feng; Qun Shen; Sumei Zhou; Yuanlin Sun; Dianzhi Hou (Food Chemistry, 2025)

Morphological and physiological responses to aridity in narrowly- and widely-distributed plant species in drylands - Junlan Xiong; Weigang Hu; Allan Degen; Jie Peng; Longwei Dong; Li Yan; Qingqing Hou; Shuran Yao; Ying Sun; Xiaoting Wang; Yahui Zhang; Yan Deng; et al. (Science China Life Sciences, 2025)

Cu+ -loaded complex adsorbent in acid modified bentonite for improving carbon monoxide (CO) capture - Jianwei Cheng; Yifan Li; Rui Zhang; Dezhi Ran; Zuyun Chen; Wenhao Hou; Qiang Fu; Zhiguang Tian (Process Safety and Environmental Protection, 2025)

Numerical investigation of the hygrothermal and energy performance of passive temperature-humidity regulation walls in various climate zones - Dongxia Wu; Zhaoyuan Shang; Jing Hou; Hailing Fu; Zhili Sun; Huan Sun; Yongan Yang; Tianlei Wang; Ran Chen; Mohammed El Ganaoui (Building and Environment, 2025)

Making waves: Sustainable control of micropollutants via NOM-mediated photosensitized activation of oxidants - Ran Yin; Xuan Hou; Senhao Lu; Chii Shang; Jinfeng Wang; Hongqiang Ren (Water Research, 2025)

Sex-dependent effects of heat exposure on the middle ear health in mice - Jie Li; Wenjun Fan; Xiangyi Yuan; Teng Wan; Li Qin; Lu Zhang; Tong Hou; Cuiqing Liu; Ran Li (Journal of Thermal Biology, 2025)

Microplastics migration mechanisms in high-erosion watersheds under climate warming - Wei Guo; Hongyang Hou; Yuzhuo Cheng; Yudan Huang; Taishan Ran; Zhaolong Zhu; Yimei Huang; Juying Jiao; Shaoshan An (Journal of Hazardous Materials, 2025)

Microbial diversity, functional properties, and flavor characteristics of high-temperature Daqu with different colors - Zhendong Zhang; Xiaoxu Ran; Zhuang Guo; Qiangchuan Hou; Dingwu Qu; Chan Wang; Yuanyuan Xu; Yurong Wang (Food Research International, 2025)

Axial compressive behaviour of seawater sea sand concrete composite columns with dual-functional C-FRCM - Linbing Hou; Ran Feng; Yuner Huang; Ying Xu; Ji-Hua Zhu (Engineering Structures, 2025)

Distribution Range and Richness of Plant Species Are Predicted to Increase by 2100 due to a Warmer and Wetter Climate in Northern China - Ying Sun; Yan Deng; Shuran Yao; Yuan Sun; Abraham Allan Degen; Longwei Dong; Jiali Luo; Shubin Xie; Qingqing Hou; Dong Tang; Yuzhen Sun; Junlan Xiong; et al. (Global Change Biology, 2025)
The warming global climate is threatening terrestrial ecosystem stability, including plant community structure and diversity. However, it remains unclear how distribution, richness, and turnover of plant species are impacted by warming and wetting in northern China. In the present study, species distribution models were applied to predict the spatial distribution of 5111 plant species based on 111,071 occurrence records in northern China. Additionally, variations in species richness and turnover rates were predicted for 2100 under 3 scenarios. The results indicated that approximately 70% of plant species will expand in their distribution, resulting in an increase in species richness. These changes will be driven mainly by temperature seasonality (TSN), annual precipitation (MAP), and mean temperature of the coldest quarter (MTCQ). However, about 30%–40% of the species will face extinction risks, including a considerable number of endemic and Red‐Listed species, and suitable habitat loss (LSH) will exceed 30%. Narrow‐ranging species will be more likely to lose a larger percentage of their suitable habitats than wide‐ranging species, highlighting their sensitivity to environmental changes. Importantly, it emerged that species turnover rates will increase linearly with ecological vulnerability at the grid level, indicating that community structure and species composition are easily affected by climate change in ecologically vulnerable areas. Therefore, biodiversity hotspots with high species richness in the southern study areas, as well as regions exhibiting both fast species turnover and significant ecological vulnerability, should be prioritized for conservation. These findings provide insights into how species composition and richness in plant communities vary with global climate change and provide effective ecological conservation and management strategies.

Modulating electron transfer in porous Cu-modified g-C3N4 for enhancing adsorption-photocatalytic synergistic removal of tetracycline hydrochloride - Ran Ma; Chunshan Li; Yumeng Su; Shengtai Hou; Wenwen Zhang; Hongjie Wang (Journal of Environmental Chemical Engineering, 2025)

Deciphering drought adaptation in Eucommia ulmoides: From the rhizosphere microbiota to root metabolites - Xueqian Zhang; Shuangshuang Hou; Xinyu Ma; Chenglong Li; Qingsong Ran; Yanfeng Han; Chunbo Dong (Applied Soil Ecology, 2025)

Synergistic improvement of straw decomposition and rice yield in saline sodic paddy soils by rational nitrogen application - Jiayong Gao; Cheng Ran; Hongming Hou; Liying Guo; Qiang Zhang; Yanqiu Geng; Xiwen Shao (Plant and Soil, 2025)

Carbon transfer from land to fluvial networks in a typical karst river-reservoir system - Yongmei Hou; Si-Liang Li; Fu-Jun Yue; Shuai Chen; Xiaolong Liu; Lishan Ran (Water Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Durable PVA-based hydrogel sponge with cellulose whiskers embedded in the 3D interconnected channels for efficient oil/water separation - Zeqi Liu; Ran Li; Yarui Hou; Juan Guo; Xiaojun Li; Kai Li; Qingye Liu (Carbohydrate Polymers, 2025)

Effects of decapitation on yield-related traits of total node number per plant in soybean - Ran Fang; Yichun Wu; Xin Huang; Zhihong Hou; Jialin Zhang; Lingshuang Wang; Yanan Wang; Yaru Li; Liyu Chen; Hui Yang; Lin Yue; Haiping Du; et al. (Field Crops Research, 2025)

A novel dual-emission fluorescence sensor with different responsive modes for non-invasive and simultaneous quantitative detection of carbaryl and imidacloprid - Yi-Fan Xia; Hou-Qun Yuan; Zhi-Qiang Cai; Le Fang; Zhen-Chong Dou; Qian-Wen Yang; Yi-Xuan Hu; Ran Wang; Yu-Fei Zhong; Guang-Ming Bao (Chemical Engineering Journal, 2025)

New insights into uranium biomineralization mediated by Pseudomonas sp. WG2-6 in the presence of organic phosphorus: Promoting effect of extracellular polymeric substance and formation of U-P nanominerals - Lin Zhou; Siyu Hou; XingQi Duan; Yalin Lu; Jiali Liao; Ning Liu; Ran Zhao; Changsong Zhao (Journal of Hazardous Materials, 2024)

Study on the degradation performance of coking wastewater using an in-situ enhanced Fe2+/Fe3+ cycle dual-cathode Electro-Fenton system - Chengwang Zhao; Yufang Ran; Yao Gong; Chen Hong; Yi Xing; Yunxiao Sun; Hao Wang; Wei Ling; Yijie Wang; Weibo Feng; Jiachen Hou; Xinlin Zhai; et al. (Journal of Environmental Chemical Engineering, 2024)

Sustainable soil rehabilitation with multifunctional mandarin orange peel/tobermorite composite hydrogels: Water retention, immobilization of heavy metals, fertilizer release and bacterial community composition - Caiqing He; Xugang Wang; Haiyan Mou; Wenjing Hou; Qilu He; Yuchen Kang; Hao Kong; Ran Li; Wenqing Chen; Tianqi Ao; Shuanjun Li; Jian Yang; et al. (Chemical Engineering Journal, 2024)

A review of bacteriophage and their application in domestic animals in a post-antibiotic era - Xinyu Guo; Guowang Luo; Fujiang Hou; Chuanshe Zhou; Xiu Liu; Zhaomin Lei; Dongyan Niu; Tao Ran; Zhiliang Tan (Science of The Total Environment, 2024)

Haploid regeneration system suitable for various genotypes of thin-skinned melons - Man Li; Yaxin Hou; Xianyang Luo; Haixiang Zhang; Fuxuan Zhou; Zhao Xie; Zongwei Hu; Jiajun Ran; Shidong Zhu (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Chronic PM2.5 exposure disrupts intestinal barrier integrity via microbial dysbiosis-triggered TLR2/5-MyD88-NLRP3 inflammasome activation - Zihan Ran; Jingcheng Yang; Liang Liu; Shaobo Wu; YanPeng An; Wanwan Hou; Tianyuan Cheng; Youyi Zhang; Yiqing Zhang; Yechao Huang; Qianyue Zhang; Jiaping Wan; et al. (Environmental Research, 2024)

Inorganic Carbon Pools and Their Drivers in Grassland and Desert Soils - Longwei Dong; Jinzhi Ran; Jiali Luo; Lin Bai; Ying Sun; Muhammad Aqeel; Yahui Zhang; Xiaoting Wang; Qiajun Du; Junlan Xiong; Haiyang Gong; Qingqing Hou; et al. (Global Change Biology, 2024)
Inorganic carbon is an important component of soil carbon stocks, exerting a profound influence on climate change and ecosystem functioning. Drylands account for approximately 80% of the global soil inorganic carbon (SIC) pool within the top 200 cm. Despite its paramount importance, the components of SIC and their contributions to CO 2 fluxes have been largely overlooked, resulting in notable gaps in understanding its distribution, composition, and responses to environmental factors across ecosystems, especially in deserts and temperate grasslands. Utilizing a dataset of 6011 samples from 173 sites across 224 million hectares, the data revealed that deserts and grasslands in northwestern China contain 20 ± 2.5 and 5 ± 1.3 petagrams of SIC in the top 100 cm, representing 5.5 and 0.76 times the corresponding soil organic carbon stock, respectively. Pedogenic carbonates (PIC), formed by the dissolution and re‐precipitation of carbonates, dominated in grasslands, accounting for 60% of SIC with an area‐weighted density of 3.4 ± 0.4 kg C m −2 at 0–100 cm depth, while lithogenic carbonates (LIC), inherited from soil parent materials, prevailed in deserts, constituting 55% of SIC with an area‐weighted density of 7.1 ± 1.0 kg C m −2 . Soil parent materials and elevation determined the SIC stocks by regulating the formation and loss of LIC in deserts, whereas natural acidification, mainly induced by rhizosphere processes including cation uptake and H + release as well as precipitation, reduced SIC (mainly by PIC) in grasslands. Overall, the massive SIC pool underscores its irreplaceable role in maintaining the total carbon pool in drylands. This study sheds light on LIC and PIC and highlights the critical impact of natural acidification on SIC loss in grasslands.

Successive application of controlled-loss urea improves grain yield and economic benefit in maize-wheat cropping systems - Lisha Shangguan; Zejie Ye; Dengke Hou; Wenlu Zhai; Zhongzhou Feng; Ran Zhang; Yingxin Xie; Geng Ma; Chenyang Wang; Dongyun Ma; Tiancai Guo; Xu Zhao (European Journal of Agronomy, 2024)

Exogenous sulfur application can effectively alleviate iron deficiency yellowing in peanuts and increase pod yield - Xiao-yan Zhang; Wen-feng Hou; Ze-chang Gou; Shu-ran Jia; Han Li; Qiang Gao; Xiao-yu Li (European Journal of Agronomy, 2024)

Salinity responsive mechanisms of sulfur-based mixotrophic denitrification and ectoine induced tolerance enhancement - Ran Li; Ya-Nan Hou; Haibo Li; Yi Han; Daohong Zhang; Yuanyuan Song; Cong Huang; Jianbo Guo; Zhihua Liu; Wei Wei; Bing-Jie Ni (Chemical Engineering Journal, 2024)

Porous carbon prepared by thermal dissolution of coal and biomass for high-performance supercapacitors - Yi Liu; Wei-Dong Cao; Xing Fan; Ran-Ran Hou; Xiang Bai; Xiao-Yun Zhang; Yan Li; Guo-Ming Zhao; Peng Liang (Fuel, 2024)

The fabrication of Mn single atoms/clusters on Al2O3 for enhanced catalytic NO oxidation - Xiao-Ke Hou; Hui-Xin Zhang; Yi-Bo Wang; Jin-Ping Zhang; Xin Gao; Lei Chen; Chao Li; Hong-Mei Jing; Chi He; Qiang Lu; Chun-Ran Chang (Fuel, 2024)

Estrogen-related receptor, a molecular target against lepidoptera pests - Guan Wang Shen; Die Liu; Hao Ran Xu; Lu Yu Hou; Jin Xin Wu; Qing You Xia; Ping Lin (Pesticide Biochemistry and Physiology, 2024)

Protective effect of ginsenoside Rb1 against aconitine cardiotoxicity studied by myocardial injury, action potential, and calcium signaling - Cuihan Zhang; Huan Hou; Changhong Shen; Qian Ran; Fang Cheng; Ziqing Yao; Ruoqi Zhang; Cheng Peng (Toxicon, 2024)

Macrophage AHR-TLR4 cross-talk drives p-STAT3 (Ser727)-mediated mitochondrial oxidative stress and upregulates IDO/ICAM-1 in the steatohepatitis induced by aflatoxin B1 - Jing Zhang; Hui Liu; Yang Shen; Dong Cheng; Hui Tang; Qi Zhang; Chao Li; Ming Liu; Wenhuan Yao; Rongrong Ran; Qingzhen Hou; Xiulan Zhao; et al. (Science of The Total Environment, 2024)

Influence of the community assemblage on sulfur distributions in the South China sea - Hao-Quan Zhang; Juan Yu; Jing-Guang Lai; Gui-Peng Yang; Long-Fei Liu; Yu Jiang; Xin-Ran Song; Yong-Qiao Chen; Hou-Jin Zhou; Qi Zhang (Marine Environmental Research, 2024)

Preferentially in-situ generated copper nanograins boosting fast kinetic conversion magnesium storage of bimetallic copper-cobalt sulfide cathode - Yaping Xia; Chunxiao Chen; Lin Ran; Hou-an Zhang; Shuai Cui; Panfei Xiao; Fei Xu; Daohong Zhang; Ting Li (Chemical Engineering Journal, 2024)

Genome constitution and evolution of Elymus atratus (Poaceae: Triticeae) inferred from cytogenetic and phylogenetic analysis - Lu Tan; Dan-Dan Wu; Chang-Bing Zhang; Yi-Ran Cheng; Li-Na Sha; Xing Fan; Hou-Yang Kang; Yi Wang; Hai-Qin Zhang; Marcial Escudero; Yong-Hong Zhou (Genes & Genomics, 2024)

Experimental optimization and mechanism analysis of extracting flavonoids with the supramolecular solvents-based methods - Zhi-lu Yu; Shi-yi Hou; Li-mei Lin; Yu-ran Chu; Ya-mei Li; Zhi-min Zhang; Jing Yan; Bo-hou Xia (Sustainable Chemistry and Pharmacy, 2024)

LRRK2 is involved in heat exposure-induced acute lung injury and alveolar type II epithelial cell dysfunction - Yindan Wang; Wenjun Fan; Guoqing Zhang; Lisha Zhao; Ting Li; Lu Zhang; Tong Hou; Huihua Hong; Zhenqiang You; Qinghua Sun; Ran Li; Cuiqing Liu (Environmental Pollution, 2024)

Fabrication of highly efficient biodegradable oligomeric lactate flame-retardant plasticizers for ultra-flexible flame-retardant poly (lactic acid) composites - Boyou Hou; Yanning Wang; Tianyang Gong; Ran Wang; Liping Huang; Bingjian Li; Jinchun Li (Chemical Engineering Journal, 2024)

Distribution and transformation characteristics of water vapor field in the fissured rock mass and its ecological significance - Danhui Su; Jianwei Zhou; Haibo Feng; Ran Li; Xiaoming Zheng; Yi Zhu; Xu Han; Qingqiu Hou (Journal of Hydrology, 2024)

Multifunctional Eu3+-MOF for simultaneous quantification of malachite green and leuco-malachite green and efficient adsorption of malachite green - Yi-Fan Xia; Hou-Qun Yuan; Chen Qiao; Wei Li; Ran Wang; Peiyao Chen; Yan-Xia Li; Guang-Ming Bao (Journal of Hazardous Materials, 2024)

Effects of nanoplastics exposure on ingestion, life history traits, and dimethyl sulfide production in rotifer Brachionus plicatilis - Juan Yu; Su Wang; Hao-Quan Zhang; Xin-Ran Song; Long-Fei Liu; Yu Jiang; Rong Chen; Qi Zhang; Yong-Qiao Chen; Hou-Jin Zhou; Gui-Peng Yang (Environmental Pollution, 2024)

Interplay between edaphic and climatic factors unravels plant and microbial diversity along an altitudinal gradient - Muhammad Aqeel; Noreen Khalid; Ali Noman; Jinzhi Ran; Abdul Manan; Qingqing Hou; Longwei Dong; Ying Sun; Yan Deng; Sang Soo Lee; Weigang Hu; Jianming Deng (Environmental Research, 2024)

Dual-emissive Eu(III)-functionalized metal-organic frameworks for visual, rapid, and intelligent sensing of albendazole and albendazole sulfoxide in animal-origin food - Hou-Qun Yuan; Yi-Fan Xia; Yu-Fei Zhong; Wei Li; Hongda Zhu; Ran Wang; Peiyao Chen; Zhiming Gao; Xiangwei Zhu; Yan-Xia Li; Guang-Ming Bao (Analytica Chimica Acta, 2024)

Multi-echo hyperspectral reflectance extraction method based on full waveform hyperspectral LiDAR - Yanhong Ran; Shalei Song; Xiaxia Hou; Yuxuan Chen; Zhenwei Chen; Wei Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Improving the photodegradation efficiency of POPs in oily sewage: Design and synthesis of G-C3N4-based photocatalysts incorporating a pickering emulsion catalytic strategy - Biyun Su; Xueqiong Ma; Liangtao Ran; Shaowei Wu; Boli Hou (Journal of Environmental Chemical Engineering, 2023)

In-situ generated elemental selenium nanograins cooperated with NiSe2 microspheres for significantly enhanced magnesium-storage performance - Changchun Hu; Lin Ran; Hou-an Zhang; Shuai Cui; Fei Xu; Daohong Zhang; Ting Li (Chemical Engineering Journal, 2023)

A sensitivity analysis framework for SMA-based self-centering systems considering uncertainty in hysteretic material parameters - Xiaoshu Gao; Canxing Qiu; Hetao Hou; Cheng Chen; Desheng Ran (Soil Dynamics and Earthquake Engineering, 2023)

RETRACTED: Variations and driving factors of leaf functional traits in the dominant desert plant species along an environmental gradient in the drylands of China - Muhammad Adnan Akram; Xiaoting Wang; Nawal Shrestha; Yahui Zhang; Ying Sun; Shuran Yao; Jinhui Li; Qingqing Hou; Weigang Hu; Jinzhi Ran; Jianming Deng (Science of The Total Environment, 2023)

Key design and layout factors influencing performance of three-way catalytic converters: Experimental and semidecoupled numerical study under real-life driving conditions - Banglin Deng; Zetao Chen; Chengqi Sun; Shoujun Zhang; Weijiao Yu; Min Huang; Kaihong Hou; Jiaqi Ran; Lili Zhou; Chao Chen; Xinxiang Pan (Journal of Cleaner Production, 2023)

Precise classification and regional delineation of maturity groups in soybean cultivars across China - Wenwen Song; Luping Liu; Shi Sun; Tingting Wu; Haiyan Zeng; Shiyan Tian; Bincheng Sun; Wenbin Li; Lijun Liu; Shuming Wang; Han Xing; Xin’an Zhou; et al. (European Journal of Agronomy, 2023)

Analysis and comparison of airflow-respirable dust control and innovative ventilation environment in drilling construction tunnels - Jinnan Guo; Angui Li; Ran Gao; Yicun Hou; Tianqi Wang; Jiaxing Li; Yifei Yin; Lunfei Che (Atmospheric Pollution Research, 2023)

Black phosphorus quantum dots induced ferroptosis in lung cell via increasing lipid peroxidation and iron accumulation - Liangding Dou; Rong Liu; Zhaojizhe Wang; Zhi Huang; Lei Wang; Mo Lin; Xin Hou; Jinwen Zhang; Tantan Cheng; Qi He; Dai Wang; Dongbei Guo; et al. (Food and Chemical Toxicology, 2023)

Multifunctional and multi-site interfacial buffer layer for efficient and stable perovskite solar cells - Pengyu Su; Huan Bi; Du Ran; Li Liu; Wenjing Hou; Guangzhao Wang; Wenbing Shi (Chemical Engineering Journal, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Theory, Technology and Practice of Unconventional Petroleum Geology - Caineng Zou; Zhi Yang; Guosheng Zhang; Rukai Zhu; Shizhen Tao; Xuanjun Yuan; Lianhua Hou; Dazhong Dong; Qiulin Guo; Yan Song; Qiquan Ran; Zhen Qiu; et al. (Journal of Earth Science, 2023)

Bio-barcode assay: A useful technology for ultrasensitive and logic-controlled specific detection in food safety: A review - Yue Hou; Ruipeng Chen; Zhiguang Wang; Ran Lu; Yonghui Wang; Shuyue Ren; Shuang Li; Yu Wang; Tie Han; Shiping Yang; Huanying Zhou; Zhixian Gao (Analytica Chimica Acta, 2023)

Microbial electrochemical technologies assisted nitrogen recovery from different wastewater sources: Performance, life cycle assessment, and challenges - Siyuan Zhai; Dexin Zhang; Wenzong Liu; Bo Wang; Bin Liang; Chengyan Liu; Ran Zeng; Yanan Hou; Hao-Yi Cheng; Aijie Wang (Resources, Conservation and Recycling, 2023)

Sesquiterpenoids from the fruits of Alpinia oxyphylla Miq. and their neuroprotective effect - Chengxing Qiu; Liping Mu; Ji Wang; Ran Tang; Bo Hou; Weiyan Hu; Rongping Zhang; Xinglong Chen (Phytochemistry, 2023)

Black phosphorus quantum dots induce autophagy and apoptosis of human bronchial epithelial cells via endoplasmic reticulum stress - Lei Wang; Mo Lin; Xin Hou; Liangding Dou; Zhi Huang; Rong Liu; Jinwen Zhang; Chuchu Cai; Chen Chen; Ying Liu; Dai Wang; Dongbei Guo; et al. (Chemosphere, 2023)

What affects the accuracy and applicability of determining wastewater sludge water content via low-field nuclear magnetic resonance? - Ya-Li Zhang; Ping Sun; Bing-Bing Dai; Shao-Ming Zheng; Dan-Di Ran; Tian-Xin Wu; Raymond Jianxiong Zeng; Hou-Feng Wang (Environmental Research, 2023)

Reverse transcription recombinase-aided amplification assay for avian influenza virus - Suchun Wang; Qingye Zhuang; Nan Jiang; Fuyou Zhang; Qiong Chen; Ran Zhao; Yang Li; Xiaohui Yu; Jinping Li; Guangyu Hou; Liping Yuan; Fuliang Sun; et al. (Virus Genes, 2023)

Chemical decontamination of foods using non-thermal plasma-activated water - Samuel Herianto; Rachelle D. Arcega; Chih-Yao Hou; How-Ran Chao; Ching-Chang Lee; Chia-Min Lin; Trias Mahmudiono; Hsiu-Ling Chen (Science of The Total Environment, 2023)

Atmospheric microplastics at a southern China metropolis: Occurrence, deposition flux, exposure risk and washout effect of rainfall - Zhen Yuan; Chenglei Pei; Hengxiang Li; Lang Lin; Shan Liu; Rui Hou; Ran Liao; Xiangrong Xu (Science of The Total Environment, 2023)

Corrigendum to “Citric acid promotes disulfide bond formation of whey protein isolate in non-acidic aqueous system” [Food Chemistry 338 (2020) 127819] - Tong Li; Jialun Hu; Ran Tian; Kaili Wang; Jinpeng Li; Abdul Qayum; Akhunzada Bilawal; Munkh-Amgalan Gantumur; Zhanmei Jiang; Juncai Hou (Food Chemistry, 2023)

TOPSIS based multi-fidelity Co-Kriging for multiple response prediction of structures with uncertainties through real-time hybrid simulation - Cheng Chen; Desheng Ran; Yanlin Yang; Hetao Hou; Changle Peng (Engineering Structures, 2023)

The eradication of biofilm for therapy of bacterial infected chronic wound based on pH-responsive micelle of antimicrobial peptide derived biodegradable microneedle patch - Xiao-Ling Lei; Kai Cheng; Yong Li; Zi-Tao Zhong; Xiao-Lin Hou; Lai-Bo Song; Fang Zhang; Jian-Hao Wang; Yuan-Di Zhao; Qiu-Ran Xu (Chemical Engineering Journal, 2023)

Lipid transformation during postmortem chilled aging in Mongolian sheep using lipidomics - Min Zhang; Rina Su; Mirco Corazzin; Ran Hou; Yue Zhang; Lina Sun; Guanhua Hu; Lu Dou; Yueying Guo; Lin Su; Lihua Zhao; Ye Jin (Food Chemistry, 2023)

Dietary pattern interfered with the impacts of pesticide exposure by regulating the bioavailability and gut microbiota - Ai Song Chen; Dong Hui Liu; Hao Nan Hou; Jia Ning Yao; Shou Chun Xiao; Xiao Ran Ma; Pei Ze Li; Qian Cao; Xue Ke Liu; Zhi Qiang Zhou; Peng Wang (Science of The Total Environment, 2023)

Photo-induced self-reduction enabling ultralow threshold voltage energy-conservation electrochromism - Zhiyuan Bai; Ran Li; Lu Ping; Qingchao Fan; Ziqiu Lu; Chengyi Hou; Qinghong Zhang; Yaogang Li; Kerui Li; Xi Ling; Hongzhi Wang (Chemical Engineering Journal, 2023)

Interfacial modulation of organic-inorganic two-dimensional superlattices for efficient electromagnetic wave absorption - Wenjian Wang; Ke Ran; Xingwang Hou; Yilin Huang; Zidong Zhang; Dongxu He; Yuan Fang; Shuai Wang; Yu Liu; Rui Zhao; Xiao-Yu Yang; Weidong Xue (Chemical Engineering Journal, 2023)

Feasibility of Surfgrass Phyllospadix iwatensis Transplantation Along the Rocky Coasts of Shandong Peninsula, China - Jiaxin Zhan; Ran Cheng; Xin Hou; Huan Wang; Peidong Zhang; Bin Kang; Wentao Li (Journal of Ocean University of China, 2022)

Legacy and emerging poly- and perfluoroalkyl substances in wastewater treatment plant and receiving water: abundance, removal, and potential ecological risk - Peng Li; Ran Yu; Feng Hou; Yuan Zhao (Environmental Science and Pollution Research, 2022)

On the K-Means Clustering Model for Performance Enhancement of Port State Control - Zeyu Hou; Ran Yan; Shuaian Wang (Journal of Marine Science and Engineering, 2022)
Nowadays, the concept of port state control is viewed as a safety net to safeguard maritime security, protect the marine environment, and ensure decent working and living circumstances for seafarers on board to a large extent. The ship can be detained for further checking if significant deficiencies are discovered during a port state control inspection. There is much research on this topic, but there have been few studies on the relationship between ship deficiencies and ship detention decisions using unsupervised machine learning artificial intelligence techniques. Although the previous methods or models are feasible for ship detention decisions, they all have shortcomings to some extent, such as large training model errors caused by the imbalance of class labels in the dataset and the fact that the training model cannot comprehensively consider all factors influencing ship detention decision due to the complexity and diversity of the problem. Unsupervised algorithms do not need to label all data in advance, and we can incorporate some fields related to port state control inspection data that can be collected into the model to allow the computer to automatically classify the ships at different risk levels according to relative criteria, e.g., the Tokyo memorandum of understanding, which may result in more objective results, thus eliminating the influence of subjective domain knowledge. It may also have more comprehensive coverage and more information on port state control inspection and decision models. Therefore, this research explores and develops an unsupervised algorithm based on k-means to improve port state control inspection decision-making models using the six-years inspection data from the Tokyo memorandum of understanding. The results show that the accuracy rate is around 50%.

Continental‐scale niche differentiation of dominant topsoil archaea in drylands - Weigang Hu; Qingqing Hou; Manuel Delgado‐Baquerizo; James C. Stegen; Qiajun Du; Longwei Dong; Mingfei Ji; Yuan Sun; Shuran Yao; Haiyang Gong; Junlan Xiong; Rui Xia; et al. (Environmental Microbiology, 2022)
Archaea represent a diverse group of microorganisms often associated with extreme environments. However, an integrated understanding of biogeographical patterns of the specialist Haloarchaea and the potential generalist ammonia‐oxidizing archaea (AOA) across large‐scale environmental gradients remains limited. We hypothesize that niche differentiation determines their distinct distributions along environmental gradients. To test the hypothesis, we use a continental‐scale research network including 173 dryland sites across northern China. Our results demonstrate that Haloarchaea and AOA dominate topsoil archaeal communities. As hypothesized, Haloarchaea and AOA show strong niche differentiation associated with two ecosystem types mainly found in China's drylands (i.e. deserts vs. grasslands), and they differ in the degree of habitat specialization. The relative abundance and richness of Haloarchaea are higher in deserts due to specialization to relatively high soil salinity and extreme climates, while those of AOA are greater in grassland soils. Our results further indicate a divergence in ecological processes underlying the segregated distributions of Haloarchaea and AOA. Haloarchaea are governed primarily by environmental‐based processes while the more generalist AOA are assembled mostly via spatial‐based processes. Our findings add to existing knowledge of large‐scale biogeography of topsoil archaea, advancing our predictive understanding on changes in topsoil archaeal communities in a drier world.

Genetic Differentiation Among Populations of Octopus minor Based on Simple Sequence Repeats Mined from Transcriptome Data - Ze Nan; Ran Xu; Chunqiang Hou; Xiaodong Zheng (Journal of Ocean University of China, 2022)

Microplastic Pollution in Nearshore Sediment from the Bohai Sea Coastline - Xiaopeng Zhu; Wen Ran; Jia Teng; Chen Zhang; Wenjing Zhang; Chaowei Hou; Jianmin Zhao; Xutong Qi; Qing Wang (Bulletin of Environmental Contamination and Toxicology, 2021)

Screening beneficial bacteriostatic lactic acid bacteria in the intestine and studies of bacteriostatic substances - Zhijing Liu; Cong Xu; Ran Tian; Wan Wang; Jiage Ma; Liya Gu; Fei Liu; Zhanmei Jiang; Juncai Hou (Journal of Zhejiang University-SCIENCE B, 2021)

Temporal variation of airborne fungi in university library rooms and its relation to environmental parameters and potential confounders - Dingmeng Wu; Ying Zhang; Chenbo Zhao; Angui Li; Li’an Hou; Yu Tian; Jing Xiong; Ran Gao (Environmental Science and Pollution Research, 2021)

Morphological and Anatomical Differences among Three Seagrass Species in a High-energy Coastal Area Typically Dominated by Surfgrass in a Rocky Coastal Area of Shandong Peninsula, China - Wen-Tao Li; Jia Song; Chongfeng Zhong; Xin Hou; Ran Cheng; Pei-dong Zhang (Ocean Science Journal, 2020)

Correction to: Description of Wenzhouxiangella salilacus sp. nov., a moderate halophilic bacterium isolated from a salt lake in Xinjiang Province, China - Shuai-Bo Han; Xin-Jun Hou; Yang-Huan Yu; Zhao Ju; Ran Zhang; Rui-Jun Wang; Yang-Hui Ye; Yan-Hu Ren; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2020)

Description of Wenzhouxiangella salilacus sp. nov., a moderate halophilic bacterium isolated from a salt lake in Xinjiang Province, China - Shuai-Bo Han; Xin-Jun Hou; Yang-Huan Yu; Zhao Ju; Ran Zhang; Rui-Jun Wang; Yang-Hui Ye; Yan-Hu Ren; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2019)

Porcine circovirus type 2 ORF5 protein induces endoplasmic reticulum stress and unfolded protein response in porcine alveolar macrophages - Yueling Ouyang; Lei Xu; Jiangman Lv; Yufeng Hou; Zhixin Fan; Panpan Xu; Yanfen Jiang; Mengmeng Wu; Ran Li; Yanming Zhang; Kangkang Guo (Archives of Virology, 2019)

Isolation and expression analysis of eight MADS-box genes in peach (Prunus persica var. nectarina ‘Luxing’) - Hui-feng Li; Qing-long Dong; Hou-zhen Jia; Gui-xiang Li; Kun Ran (Journal of Plant Biochemistry and Biotechnology, 2018)

Evaluation of ocean-atmospheric indices as predictors for summer streamflow of the Yangtze River based on ROC analysis - Ran-Ran He; Yuanfang Chen; Qin Huang; Sheng-Nan Yu; Yong Hou (Stochastic Environmental Research and Risk Assessment, 2018)

Protodioscin ameliorates oxidative stress, inflammation and histology outcome in Complete Freund’s adjuvant induced arthritis rats - Jia-Yu Liu; Ya-Ling Hou; Rong Cao; Hong Xia Qiu; Guo-Hua Cheng; Ran Tu; Li Wang; Jun-Li Zhang; Dan Liu (Apoptosis, 2017)

Distribution of primary school based on spatial network comprehensive model in low-income mountainous cities: a case study in Wanyuan, China - Pei-feng Yang; Ran He; Hai-bo Hou (Journal of Mountain Science, 2017)

Molecular cloning and its expression of trachealess gene (As-trh) during development in brine shrimp, Artemia sinica - Jia-Qing Wang; Lin Hou; Nan Yi; Riu-Feng Zhang; Xiang-Yang Zou; Qin Xiao; Ran Guo (Molecular Biology Reports, 2012)

A “GC-rich” method for mammalian gene expression: A dominant role of non-coding DNA GC content in regulation of mammalian gene expression - Qian Jia; HongTao Wu; XingJun Zhou; Jian Gao; Wei Zhao; JouDi Aziz; JingShuang Wei; Lihua Hou; Shuyin Wu; Ying Zhang; XiangFeng Dong; YanMin Huang; et al. (Science China Life Sciences, 2010)

Changes in morphology and biochemical indices in browning callus derived from Jatropha curcas hypocotyls - Yang He; Xiulian Guo; Ran Lu; Bei Niu; Vijaya Pasapula; Pei Hou; Feng Cai; Ying Xu; Fang Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)